(untitled) (Revista Brasileira Multidisciplinar, 2026)
The contemporary scenario has seen significant changes with the use of facilitating tools in the cytology teaching-learning process. Given this context, it is necessary for teachers to be able to respond to the recurring methodological diversities in the classroom. In light of this, this review chapter aims to provide information on the implementation of active methodologies in the classroom, focusing on the use of mind maps and schematic models. Based on the discussions proposed by various authors, it is evident that the use and implementation of these active methodologies make classes more dynamic, interactive, and engaging. Additionally, it is important to emphasize that these resources, while providing opportunities for students, also enrich classes by enabling them to visualize concepts, fostering better understanding through scientific validation of the subject.